2001
DOI: 10.1289/ehp.01109515
|View full text |Cite
|
Sign up to set email alerts
|

Diesel exhaust particles suppress macrophage function and slow the pulmonary clearance of Listeria monocytogenes in rats.

Abstract: In this study, we tested the hypothesis that exposure to diesel exhaust particles (DEP) may increase susceptibility of the host to pulmonary infection. Male Sprague-Dawley rats received a single dose of DEP (5 mg/kg), carbon black (CB, 5 mg/kg), or saline intratracheally. Three days later, the rats were inoculated intratracheally with approximately 5,000 Listeria monocytogenes and sacrificed at 3, 5, and 7 days postinfection, and we determined the number of viable Listeria in the left lobe of lungs. The remain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
65
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 109 publications
(69 citation statements)
references
References 51 publications
(47 reference statements)
3
65
1
Order By: Relevance
“…This may explain the caspase activation that was seen at 24 h postexposure in RAW cells ( Figure 7A). Macrophage dysfunction and toxicity from particle overload were observed in several previous studies, where cells preloaded with various particles can not perform their phagocytic duty (Lundborg et al, 2006;Zhou and Kobzik, 2007;Yang et al, 2001;Oberdorster, 1995) and succumb to toxicity from the engulfed particles (Allison et al, 1966;Hiura et al, 1999;Li et al, 2002).…”
Section: Discussionmentioning
confidence: 93%
“…This may explain the caspase activation that was seen at 24 h postexposure in RAW cells ( Figure 7A). Macrophage dysfunction and toxicity from particle overload were observed in several previous studies, where cells preloaded with various particles can not perform their phagocytic duty (Lundborg et al, 2006;Zhou and Kobzik, 2007;Yang et al, 2001;Oberdorster, 1995) and succumb to toxicity from the engulfed particles (Allison et al, 1966;Hiura et al, 1999;Li et al, 2002).…”
Section: Discussionmentioning
confidence: 93%
“…On the other hand, Saxena and coworkers showed that exposure of mouse AMs to diesel exhaust particles attenuated IFN-ginduced production of NO (36). In addition, pulmonary exposure of rats to diesel exhaust particles depressed NO production by AMs in response to pulmonary LM infection and depressed bacterial clearance (37). Similarly, pulmonary exposure to ROFA enhanced zymosan-stimulated chemiluminescence in rat AMs but reduced NO release and bacterial clearance in response to the same stimulus (38).…”
Section: Discussionmentioning
confidence: 99%
“…There are reports, however, of increased numbers of hospitalizations for respiratory disorders including infections on days of increased levels of PM (2). In support of these epidemiologic findings, several rodent models have shown PM exposure can increase susceptibility to infectious bacteria such as Listeria monocytogenes and Streptococcus pneumoniae (3,4).…”
mentioning
confidence: 93%